In spite of the clarity of mental health and psychosocial core principles: the existence of a participation implementation gap. Issue 3 (November 2016) - Besselink, Djoen
Abstract : According to humanitarian minimal standards, humanitarian programmes should maximise participation of affected populations within their response. Participation has been a key point in proposals, evaluators are aware of it and every aid worker has heard of it. In theory, it is a perfectly implemented, well understood and a well respected construct. In the field of mental health and psychosocial support, participation is core principle number two. Based on personal observations, this paper will delve deeper into the concept of participation within mental health and psychosocial support and the importance of its implementation. Further, and perhaps more importantly, it will reflect on the fact that even though this concept is so imbedded into concepts of humanitarian aid, there is a huge implementation gap. As a result, this paper also calls for action to fill this implementation gap and improve humanitarian aid through the principle of participation.